Mechanistic insight in site-selective and anisotropic etching of prussian blue analogues toward designable complex architectures for efficient energy storage. Issue 20 (13th May 2020) - Xu, Hai; Zhao, Xi; Yu, Chenyang; Sun, Yue; Hui, Zengyu; Zhou, Ruicong; Xue, Jialu; Dai, Henghan; Zhao, Yue; Wang, Lumin; Gong, Yujiao; Zhou, Jinyuan; et al.
Abstract : Two distinct regions formed inside NCP cubes determine the position and anisotropic pathway of subsequent chemical etching. Abstract : Engineering coordination compounds, e.g., prussian blue (PB) and its analogues (PBAs), with designable complex nanostructures via chemical etching holds great opportunities for improving energy storage performances by adjusting topological geometry, selectively exposing active sites, tuning electronic properties and enhancing accessible surface area. Unfortunately, it remains ambiguous particularly on site-selective and anisotropic etching behaviors. Herein, for the first time, we propose that two distinct regions are formed inside NiCo PBA (NCP) cubes due to the competition between classical ion-by-ion crystallization and non-classical crystallization based on aggregation. Such a unique structure ultimately determines not only the etching position but also the anisotropic pathway by selectively exposing unprotected Ni sites. According to this principle, complex PBA architectures, including nanocages, open nanocubes (constructed by six cones sharing the same apex), nanocones, and chamfer nanocubes can be intentionally obtained. After thermal annealing, NCP nanocones are converted to morning glory-like porous architectures composed of NiO/NiCo2 O4 heterostructures with a mean particle size of 5 nm, which show improved rate performance and cycling stability.